School adaptation and adolescent immigrant mental health: Mediation of positive academic emotions and conduct problems - Xie, Lingping; Zou, Weixing; Wang, Hongli (Frontiers in Public Health, 2022)
Immigrant adolescents must adapt their physical and mental attitudes to attain healthy development due to dramatic changes in their living and learning environments after relocation. From the perspective of positive psychology, this study explored the specific influence of school adaptation on mental health among immigrant adolescents, mainly focusing on the mediating effects of positive academic emotions and conduct problems. We selected primary and secondary school students from five relocated resettlement schools in Qianxinan Buyi and Miao Autonomous Prefecture, which has the largest population of relocated people in Guizhou Province, China. Using cluster sampling, 550 relocated students in Grades 5-12 from the five schools were recruited to complete a battery of questionnaires, including the Immigrant Adolescents' School Adaptation Scale, the General Health Scale, and the Positive Academic Emotions Questionnaire, and the Adolescents' Behavioral Tendency Questionnaire. In addition, this study used the bias-corrected Bootstrap method to explore the chain-mediating effect of positive academic emotions and conduct problems between school adaptation and mental health. The results showed that immigrant adolescents have significant gender differences only in conduct problems. However, significant learning stage differences exist in school adaptation, mental health, positive academic emotions, and conduct problems. School adaptation, positive academic emotions, and mental health were significantly positively correlated. In contrast, conduct problems were significantly negatively correlated with mental health. School adaptation influenced mental health through the mediation effects of positive academic emotions and conduct problems. These effects contained three paths: the separate mediation effects of positive academic emotions and conduct problems and the chain mediation effect of positive academic emotions and conduct problems.